Analysis of Factors that Influence APBD Revenues in Regencies/Cities across the Nias Islands - Adilman Baradarkhasan Zega (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
This study aims to determine how much influence per capita GRDP, education level, and health level have on district/city APBD revenues throughout the Nias archipelago in 2012 - 2022. The type of research used is descriptive quantitative. The data used is secondary data. This research is a panel data study with the panel data regression analysis method carried out with Eviews 12.0. The results showed that per capita GRDP, education level, and health level variables had a positive effect on district/city APBD revenues for the Nias archipelago in 2012 – 2022.